Strategi Digital PT. Golpra Putra Lubsa: Pembuatan Katalog untuk Meningkatkan Pemasaran dan Penjualan Terhadap Lokal Maupun Global - Leona, Merlin (Universitas Serambi Mekkah, 2024)
PT Golpra Putra Lubsa, a distribution company established in 2008, faces challenges in operational and marketing processes due to manual order recording methods and the lack of a digital platform. The main problems include inefficient recording systems, limited marketing reach, and minimal communication channels with customers. To address these issues, a digital catalog and website development project was undertaken using the Multimedia Development Life Cycle (MDLC) method, which includes six stages: concept, design, material collection, assembly, testing, and distribution. The project resulted in a product catalog created using Canva Pro Studio and a website developed through Wix, encompassing home page, vision mission, product catalog, online ordering, and contact pages. The implementation of this digital system provides significant improvements in operational efficiency, ease of product information access, and potential for broader market reach, both locally and globally. Evaluation shows increased customer satisfaction and simplified ordering processes. Recommendations for further development include periodic updates to the website and catalog, and continued optimization of digital strategies to support company growth.